Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To convert the given equation from standard form to graphing form, we will use the method of completing the square.
The given equation is:
[tex]\[ x^2 - 6x + y^2 - 4y + 12 = 0 \][/tex]
### Step-by-Step Solution
1. Group the [tex]\(x\)[/tex] terms and the [tex]\(y\)[/tex] terms together:
[tex]\[ (x^2 - 6x) + (y^2 - 4y) + 12 = 0 \][/tex]
2. Complete the square for the [tex]\(x\)[/tex] terms:
[tex]\[ x^2 - 6x = (x - 3)^2 - 9 \][/tex]
3. Complete the square for the [tex]\(y\)[/tex] terms:
[tex]\[ y^2 - 4y = (y - 2)^2 - 4 \][/tex]
4. Substitute these squares back into the equation:
[tex]\[ (x - 3)^2 - 9 + (y - 2)^2 - 4 + 12 = 0 \][/tex]
5. Simplify the constant terms:
[tex]\[ (x - 3)^2 + (y - 2)^2 - 9 - 4 + 12 = 0 \][/tex]
[tex]\[ (x - 3)^2 + (y - 2)^2 - 1 = 0 \][/tex]
6. Move the constant term to the right side of the equation:
[tex]\[ (x - 3)^2 + (y - 2)^2 = 1 \][/tex]
The converted equation is now in graphing form:
[tex]\[ (x - 3)^2 + (y - 2)^2 = 1 \][/tex]
This matches the option:
c [tex]\((x - 3)^2 + (y - 2)^2 = 1\)[/tex]
Thus, the correct answer is:
[tex]\[ \boxed{\text{c}} \][/tex]
The given equation is:
[tex]\[ x^2 - 6x + y^2 - 4y + 12 = 0 \][/tex]
### Step-by-Step Solution
1. Group the [tex]\(x\)[/tex] terms and the [tex]\(y\)[/tex] terms together:
[tex]\[ (x^2 - 6x) + (y^2 - 4y) + 12 = 0 \][/tex]
2. Complete the square for the [tex]\(x\)[/tex] terms:
[tex]\[ x^2 - 6x = (x - 3)^2 - 9 \][/tex]
3. Complete the square for the [tex]\(y\)[/tex] terms:
[tex]\[ y^2 - 4y = (y - 2)^2 - 4 \][/tex]
4. Substitute these squares back into the equation:
[tex]\[ (x - 3)^2 - 9 + (y - 2)^2 - 4 + 12 = 0 \][/tex]
5. Simplify the constant terms:
[tex]\[ (x - 3)^2 + (y - 2)^2 - 9 - 4 + 12 = 0 \][/tex]
[tex]\[ (x - 3)^2 + (y - 2)^2 - 1 = 0 \][/tex]
6. Move the constant term to the right side of the equation:
[tex]\[ (x - 3)^2 + (y - 2)^2 = 1 \][/tex]
The converted equation is now in graphing form:
[tex]\[ (x - 3)^2 + (y - 2)^2 = 1 \][/tex]
This matches the option:
c [tex]\((x - 3)^2 + (y - 2)^2 = 1\)[/tex]
Thus, the correct answer is:
[tex]\[ \boxed{\text{c}} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.